Understanding vaccination gaps in Peru: a convergent cross-sectional analysis of coverage, parental perceptions, and child mortality data in Sunampe - Margarita Norma Castro-Fuentes; Carlos Andrés Mugruza-Vassallo (Frontiers in Public Health, 2026)
Background The Sunampe district on the Peruvian coast faces challenges related to adherence to childhood vaccination schedules. This study aimed to assess whether non-compliance with vaccination correlates with an increased risk of vaccine-preventable epidemiological vulnerability and health system fragility among children under five, within the context of low coverage in Sunampe. Methods An analytical, correlational, cross-sectional study was conducted involving 123 families in Sunampe. Data on vaccination status, reported illnesses, and mortality of children aged 1 to 5 years were collected. Medical records were reviewed for vaccine-preventable diseases, and mortality data were obtained from the SINADEF database. Severe non-compliance was defined as vaccination discontinued by 6 months of age (≥3 missed key doses). Logistic regression with prespecified predictors (knowledge, fear, access) was used to identify determinants of severe non-compliance. Mortality data were obtained from the SINADEF database (2017–2022). Sensitivity analysis using Firth’s penalized logistic regression with dimension reduction (composite knowledge, fear, and access scores) addressed low events-per-variable (EPV = 4.5). Results Some Peruvian districts had to improve health facilities, while families in Sunampe perceived the single local health center as insufficient. No active vaccine-preventable illnesses were reported among surveyed children, but SINADEF data showed 10 deaths in children under five between 2017 and 2022, including 6 around respiratory mechanics issues (Pneumococcus) and 1 with malnutrition (no clearly anemia). Also, it was shown the prevalence of illness and incomplete immunization, as well as increased rates of anemia in Peru. Logistic regression models had fair to good predictive power and identified two significant predictors of severe non-compliance: lack of knowledge about vaccination age (Q17: OR = 10.96, 95% CI: 3.40–35.36, p = 0.0001) and never attending a vaccine information session (Q18: OR = 3.32, 95% CI: 1.16–9.57, p = 0.026). Fear of reactions (reported by 99.2% of mothers) did not reach statistical significance. The model showed good discriminative ability (AUC = 0.852, accuracy = 76.4%). Firth penalized logistic regression on composite scores confirmed knowledge as the only significant predictor (OR = 3.84 per 1-point increase, p < 0.001), while fear (OR = 2.82, p = 0.082) and access (OR = 0.80, p = 0.512) were not significant. Conclusion Incomplete vaccination in Sunampe appears linked to parental knowledge gaps and concerns about vaccine side effects, despite most parents reporting no severe reactions. Fear of reactions did not predict behavior, suggesting that reported safety concerns may reflect social desirability bias rather than true barriers. These findings highlight the need, in clinical decision-making, for targeted education to improve vaccination adherence and reduce epidemiological vulnerability and health system fragility.